Effects of the Selected Smartphone Social-Messaging Applications Training on Iranian Elderly's Quality of Life: Results of a Qualitative Study - Hosseini, Seyed Ebrahim; Charters, Stuart; Anthony, Patricia; Alhazmi, Abdulsalam (International Association of Online Engineering (IAOE), 2021)
This qualitative study investigates the effects of training in selected smartphone social-messaging applications on the quality of life of Iranian elderly people. The study explores how learning and using smartphone messaging applications can influence social communication, independence, and perceived quality of life among elderly participants.